Disclosure of Sexual Intercourse by Teenagers: Agreement Between Telephone Survey Responses and Annual Visit Disclosures. (June 2015) - Alexander, Stewart C.; Fortenberry, J. Dennis; Pollak, Kathryn I.; Østbye, Truls; Bravender, Terrill; Tulsky, James A.; Dolor, Rowena; Shields, Cleveland G.
Background . Physicians can help guide teenagers in their emerging sexuality; however, teens rarely inform physicians about their sexual activity. Methods . We audio-recorded annual visits between 365 teenagers and 49 physicians. Before the recorded visit, the teens were asked in a confidential telephone survey whether they had ever engaged in sexual intercourse. Recordings were coded for teenage disclosures about previous sexual intercourse. We measured agreement between telephone survey responses and annual visit disclosures, and examined factors associated with agreement between the two. Results . Fifty-six teenagers (15%) reported previous sexual intercourse in either the telephone survey or to their physician. Among those who reported sexual intercourse, 57% shared this information to both the telephone survey and their physician (κ = .72, confidence interval = 0.63-0.82). Conclusions . Although a slight majority of teenagers disclosed their sexual activity to both the telephone survey and their doctor, a significant number disclosed to just one source.